Composite porous material as well as preparation method and application thereof
By immersion porous sound absorption materials in high-content nano fiber water dispersing solution and freeze and dry treatment, a multi-level micro-nanocarium composite pores are formed, which solves the problem of poor sound absorption effect of porous sound absorption materials. A significant improvement of sound absorption effect is achieved.
Patent Information
- Application Number
- CN202411242318.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-21
AI Technical Summary
The sound absorption effect of existing porous sound absorption materials is poor, and the existing methods to improve sound absorption effect are relatively complex or have limited effects.
By soaking the porous sound-absorbing material in a high-content nanofiber aqueous dispersion and freeze-drying it, multi-layered micro-nano composite pores are formed to enhance the dissipation of sound energy.
The sound absorption effect of composite porous materials is significantly improved, especially in the low frequency range, and the process is simple and easy to operate, making it suitable for mass production.
Smart Images

Figure CN119331303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound absorbing materials, and more specifically, to a composite porous material and a preparation method and application thereof. Background Art
[0002] Noise pollution is the third largest environmental pollution after air and water pollution. It not only causes neurosis such as neurasthenia, insomnia, headache, but also leads to obvious health problems such as blood circulation, heart and balance disorders, and even affects the fetus in the womb of pregnant women. In addition, noise will also have a serious impact on the use of instruments and equipment. Strong noise can cause mechanical accidents due to acoustic fatigue fracture, and damage buildings. Designing and manufacturing high-performance sound-absorbing materials is one of the feasible ways to reduce noise pollution.
[0003] Currently, commercial sound-absorbing materials are mainly divided into two categories: resonant sound-absorbing materials and porous sound-absorbing materials. Among them, porous sound-absorbing materials (such as foam) convert sound energy into heat energy and dissipate it through the effects of friction resistance, viscous resistance and heat conduction generated when sound waves propagate in their pores, thereby achieving the purpose of sound absorption and noise reduction. At the same time, porous sound-absorbing materials are low-cost and easy to manufacture on a large scale at low cost. They are suitable for large venues such as theaters, concert halls, performance theaters, stations, airports, etc. However, the sound absorption and noise reduction effect of a single porous sound-absorbing material is relatively limited, so it is usually necessary to modify it to further improve the sound absorption and noise reduction effect.
[0004] A Chinese patent titled "A polyvinylidene fluoride composite foam sound-absorbing material, its preparation method and application" first mixes the foam material solution and the fiber material solution, then adds white sugar, and then solidifies to obtain the composite foam sound-absorbing material. The introduction of fiber material improves the sound absorption performance of the foam material, but the patent requires a foam material solution as a raw material, and the preparation process is relatively complicated.
[0005] A Chinese patent titled "A polymer sponge sound-absorbing composite material and its preparation method" uses flaky graphene oxide films and carbon nanotubes to be doped into the skeleton openings of porous sound-absorbing materials to form a semi-open-pore structure to enhance the sound absorption effect. However, this semi-open-pore structure blocks the propagation path of sound waves inside the material to a certain extent, resulting in limited improvement in the sound absorption effect.
[0006] In addition, according to the dissipation theory, the dissipation force is a linear function of the rate, and the dissipation power is the product of the force and the flow rate, that is, the dissipation power is a quadratic function of the frequency. Therefore, more attention needs to be paid to the sound absorption effect of porous sound-absorbing materials on noise with a frequency <2kHz (the main band of urban noise). Summary of the invention
[0007] The primary purpose of the present invention is to overcome the problem that the sound absorption effect of the above-mentioned existing porous sound-absorbing materials is poor or the existing methods for improving the sound absorption effect of porous sound-absorbing materials are relatively complicated or the improvement effect is limited, and to provide a method for preparing a composite porous material.
[0008] A further object of the present invention is to provide a composite porous material.
[0009] A further object of the present invention is to provide an application of the composite porous material in preparing sound absorbing products.
[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0011] A method for preparing a composite porous material comprises the following steps:
[0012] The porous sound-absorbing material is immersed in the nanofiber aqueous dispersion, then taken out and freeze-dried to obtain the composite porous material;
[0013] The mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 5 to 25 g:1 L;
[0014] The pore size of the porous sound absorbing material is in micron order.
[0015] The existing technology uses nanofibers and other materials (such as graphene) to modify porous sound-absorbing materials to improve the sound absorption effect, wherein the nanofibers and other materials need to be prepared together into a mixed solution / dispersion, and the amount of nanofibers in the mixed solution / dispersion is usually low.
[0016] The inventors of the present invention have found that the sound absorption effect of the composite porous material can be improved to a certain extent by using only nanofibers and preparing a nanofiber aqueous dispersion with a high content (mass volume ratio of 5 to 25g: 1L), soaking the porous sound-absorbing material with the nanofiber aqueous dispersion, and performing conventional drying (room temperature or high temperature). This is because: a higher nanofiber content can increase the void level of the porous sound-absorbing material and generate more friction resistance to noise. However, the nanofiber content of the nanofiber aqueous dispersion cannot be further increased, otherwise the viscosity of the dispersion will be too high. When soaking the porous sound-absorbing material, the nanofibers are blocked from entering the voids of the porous sound-absorbing material, resulting in uneven distribution of the nanofibers in the porous sound-absorbing material. Therefore, the degree of improvement in the sound absorption effect is still limited by only using a high-content nanofiber aqueous dispersion to soak the porous sound-absorbing material.
[0017] The inventors of the present invention have further studied and found that by soaking the porous sound-absorbing material in a high-content nanofiber aqueous dispersion and then freeze-drying to remove water, the frozen water in the freeze-drying process will be removed by sublimation, which avoids the nanofibers overlapping on the skeleton of the porous sound-absorbing material due to the surface tension of the liquid to form a thin film and block the holes during room temperature drying or high temperature drying, thereby forming multi-level micro-nano composite pores, greatly increasing the specific surface area and pore tortuosity of the material, enhancing the dissipation of sound energy, and thus significantly improving the sound absorption effect of the composite porous material. In addition, the preparation method of the present invention also significantly improves the low-frequency sound absorption effect of the composite porous material.
[0018] In addition, the preparation method of the present invention has simple process and convenient operation, which is conducive to the mass production of composite porous materials; the nanofiber aqueous dispersion of the present invention uses water as a dispersant, and does not require the use of other toxic and harmful reagents, and the manufacturing process is safe and environmentally friendly.
[0019] In the present invention, the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion can be 5g:1L, 8g:1L, 10g:1L, 12g:1L, 15g:1L, 18g:1L, 20g:1L, 22g:1L or 25g:1L.
[0020] Preferably, the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 10-20 g:1L.
[0021] By regulating the content of nanofibers in the nanofiber aqueous dispersion within this range, the obtained composite porous material has a better sound absorption effect.
[0022] Preferably, the preparation process of the nanofiber aqueous dispersion is: adding nanofibers and a dispersing aid into water, dispersing them, and obtaining a uniform nanofiber aqueous dispersion.
[0023] Any dispersing aid that facilitates the dispersion of nanofibers in water can be used in the present invention.
[0024] More preferably, the dispersing aid is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, alkyl fatty alcohol polyoxyethylene ether, fatty amine polyoxyethylene ether, alkyl alcohol amide polyoxyethylene ether, block polyoxyethylene-polyoxypropylene ether, alkyl alcohol amide or polyvinyl pyrrolidone.
[0025] More preferably, the mass ratio of the nanofibers to the dispersing aid is 1:(0.8-1.2).
[0026] More preferably, the dispersion method is at least one of shaking, stirring or ultrasound.
[0027] More preferably, the power of the ultrasound is 500-900 W, and the time is 5-80 min.
[0028] Preferably, the aspect ratio of the nanofiber is (10-5000):1.
[0029] Preferably, the nanofiber has a morphology of at least one of a nanotube or a nanowire.
[0030] More preferably, the nanotube is at least one of carbon nanotube, silicon carbide nanotube or titanium dioxide nanotube.
[0031] More preferably, the nanowire is at least one of copper nanowire, silver nanowire, gold nanowire or zinc oxide nanowire.
[0032] Preferably, the material of the nanofiber is at least one of carbon, copper, silver, gold, zinc oxide or titanium dioxide.
[0033] Preferably, the porous sound-absorbing material is at least one of polymer foam, cellulose board material or inorganic porous material.
[0034] More preferably, the porous sound absorbing material is polymer foam.
[0035] By selecting polymer foam, the obtained composite porous material still has good sound absorption effect after compression.
[0036] Further preferably, the polymer foam is at least one of melamine foam, polyurethane foam or polyester foam.
[0037] More preferably, the cellulose material board is at least one of a wooden board or a cotton and linen board.
[0038] More preferably, the inorganic porous material is at least one of zeolite, limestone, concrete, foamed aluminum, foamed nickel or foamed copper.
[0039] Preferably, the porosity of the porous sound absorbing material is ≥30%, and may be 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 98% or 99%, preferably 30-90%.
[0040] Preferably, the macroscopic shape of the porous sound-absorbing material is at least one of a film shape, a pyramid shape, a groove shape, a polygonal column shape, a polygonal pyramid shape, a cylinder shape, a cone shape, a hemisphere shape, a sphere shape, a ring shape or an irregular shape.
[0041] More preferably, the macroscopic shape of the porous sound absorbing material is a film shape.
[0042] Preferably, the thickness of the porous sound absorbing material is 1 to 1000 mm.
[0043] More preferably, the thickness of the porous sound absorbing material is 10-100 mm.
[0044] Preferably, the soaking time is 15 to 100 minutes.
[0045] Preferably, the freeze-drying temperature is -70 to -18°C.
[0046] Preferably, the freeze-drying time is 30 to 500 minutes.
[0047] Preferably, the porous sound absorbing material has a pore size distribution of 10 to 800 μm.
[0048] A composite porous material is prepared by the above preparation method.
[0049] The application of the above-mentioned composite porous material in the preparation of sound-absorbing products also falls within the protection scope of the present invention.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The present invention soaks the porous sound-absorbing material in a nanofiber aqueous dispersion, takes it out and then removes the water by freeze-drying, so that the porous sound-absorbing material can effectively load the nanofibers and form multi-level micro-nano composite pores, which significantly improves the sound absorption effect of the composite porous material. In addition, the preparation method of the present invention also significantly improves the low-frequency sound absorption effect of the composite porous material. In addition, the composite porous material can also have the characteristics of light weight and low price.
[0052] In addition, the preparation method of the present invention has simple process and convenient operation, which is conducive to the mass production of composite porous materials; the nanofiber aqueous dispersion of the present invention uses water as a dispersant, and does not require the use of other toxic and harmful reagents, and the manufacturing process is safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a scanning electron microscope image (low magnification) of the composite porous material of Example 1.
[0054] Figure 2 This is a scanning electron microscope image (high magnification) of the composite porous material of Example 1.
[0055] Figure 3 This is a comparison chart of the sound absorption coefficients of the composite porous material of Example 6 and the melamine foam of Comparative Example 4. DETAILED DESCRIPTION
[0056] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0057] Example 1
[0058] This embodiment provides a method for preparing a composite porous material, comprising the following steps:
[0059] The nanofibers and the dispersing aid were added into water, and ultrasonic (power of 800W, time of 60min) was applied to obtain a uniform nanofiber aqueous dispersion; then the melamine foam was immersed in the nanofiber aqueous dispersion for 15min, taken out, and freeze-dried (-60℃, 3h) to obtain a composite porous material;
[0060] Among them, the nanofibers are multi-walled carbon nanotubes, and the aspect ratio of the multi-walled carbon nanotubes is 1000:1; the mass volume ratio of nanofibers and water in the nanofiber aqueous dispersion is 20g:1L; the dispersing aid is fatty amine polyoxyethylene ether, and the mass ratio of nanofibers to the dispersing aid is 1:1; the thickness of the melamine foam is 10mm, and its pore size distribution is 80-300μm.
[0061] Example 2
[0062] This embodiment provides a method for preparing a composite porous material, which is different from Embodiment 1 in that: multi-walled carbon nanotubes are replaced by copper nanowires with an aspect ratio of 2000:1; melamine foam is replaced by polyurethane foam with a pore size distribution of 200 to 600 μm.
[0063] Example 3
[0064] This embodiment provides a method for preparing a composite porous material, which is different from Embodiment 1 in that: multi-walled carbon nanotubes are replaced by silver nanowires, whose aspect ratio is 4000:1; melamine foam is replaced by polyester foam, whose pore size distribution is 200-600 μm.
[0065] Example 4
[0066] This embodiment provides a method for preparing a composite porous material, which is different from Embodiment 1 in that: multi-walled carbon nanotubes are replaced by zinc oxide nanowires, whose aspect ratio is 200:1; melamine foam is replaced by cotton and linen board material, whose pore size distribution is 300-800 μm.
[0067] Example 5
[0068] This embodiment provides a method for preparing a composite porous material, which is different from Embodiment 1 in that: multi-walled carbon nanotubes are replaced by silicon carbide nanotubes, whose aspect ratio is 100:1; melamine foam is replaced by concrete, whose pore size distribution is 10 to 300 μm.
[0069] Example 6
[0070] This embodiment provides a method for preparing a composite porous material. The difference from Embodiment 1 is that the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 10 g:1 L.
[0071] Example 7
[0072] This embodiment provides a method for preparing a composite porous material. The difference from Embodiment 1 is that the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 5 g:1 L.
[0073] Comparative Example 1
[0074] This comparative example provides a method for preparing a composite porous material, which is different from Example 1 in that the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 1 g:1 L.
[0075] Comparative Example 2
[0076] This comparative example provides a method for preparing a composite porous material, which is different from Example 1 in that the mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 40 g:1 L.
[0077] Comparative Example 3
[0078] This comparative example provides a method for preparing a composite porous material, which is different from Example 1 in that freeze drying is adjusted to heating drying (50° C., 3 h).
[0079] Comparative Example 4
[0080] This comparative example provides melamine foam without any treatment (ie, the melamine foam before being immersed in the multi-walled carbon nanotube dispersion in Example 1).
[0081] Performance Testing
[0082] 1. The composite porous material of Example 1 was tested by scanning electron microscope. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that after freeze drying, the gaps between the nanofibers and the porous sound-absorbing material form multi-layered micro-nanoscale composite pores. Further increasing the magnification of the electron microscope, we can obtain Figure 2 ,from Figure 2 It can be seen that the nanofibers are entangled with each other to form countless nanoscale pores, thereby constructing more complex pores in a relatively simple micron-scale foam skeleton.
[0083] 2. The composite porous materials of Examples 1 to 7 and Comparative Examples 1 to 3 and the melamine foam of Comparative Example 4 were tested for sound absorption coefficient. The composite porous materials of Examples 1 to 3, 6 to 7 and Comparative Examples 1 to 3 and the melamine foam of Comparative Example 4 were tested for sound absorption coefficient after compression. The test method is as follows:
[0084] 1) Sound absorption coefficient test
[0085] The standing wave tube method is used. The sample is placed in a standing wave tube, and the sound absorption coefficient of each sound wave frequency (1300Hz, 1600Hz, 2000Hz, 2500Hz, 3150Hz, 4000Hz, 5000Hz, 6300Hz) in the standing wave tube is tested by moving the position of the microphone, and the average sound absorption coefficient of the entire frequency band is further calculated.
[0086] 2) Sound absorption coefficient test after compression
[0087] The standing wave tube method is used. The sample is placed in a universal tensile testing machine and compressed 10,000 times. The external morphology of the sample does not change. The sample after the compression cycle test is placed in a standing wave tube. By moving the position of the microphone, the sound absorption coefficient of each sound wave frequency (1300Hz, 1600Hz, 2000Hz, 2500Hz, 3150Hz, 4000Hz, 5000Hz, 6300Hz) in the standing wave tube is tested, and then the average sound absorption coefficient of the whole frequency band is calculated.
[0088] The test results are shown in Table 1.
[0089] Table 1 Test results of sound absorption coefficient of samples in various embodiments and comparative examples
[0090]
[0091] As can be seen from Table 1, the full-band average sound absorption coefficients (before cyclic compression) of the composite porous materials of Examples 1 to 7 are all above 0.660, the high-frequency (6300 Hz) sound absorption coefficients are all above 0.9, and the low-frequency (1300 Hz) sound absorption coefficients are all above 0.340, indicating that the present invention effectively improves the sound absorption effect of the composite porous material after immersion in a high-content nanofiber aqueous dispersion and freeze-drying treatment.
[0092] The nanofiber content of the nanofiber aqueous dispersion of Comparative Example 1 is too low, which is not conducive to the formation of multi-level micro-nano composite pores, and the sound absorption effect of the high frequency, low frequency and full frequency band of the composite porous material is poor, especially the sound absorption effect of the low frequency is poor. The nanofiber content of the nanofiber aqueous dispersion of Comparative Example 2 is too high, and the sound absorption effect of the high frequency, low frequency and full frequency band of the composite porous material is poor, and the sound absorption effect of the full frequency band after cyclic compression is significantly reduced. Comparative Example 3 is heated and dried, and the sound absorption effect of the high frequency and full frequency band of the composite porous material is not increased, and the sound absorption effect of the low frequency is poor.
[0093] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite porous material, characterized in that: The steps include: The porous sound-absorbing material is immersed in the nanofiber aqueous dispersion, then taken out and freeze-dried to obtain the composite porous material; The mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 5 to 25 g:1 L; The pore size of the porous sound absorbing material is in micron order.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of nanofibers to water in the nanofiber aqueous dispersion is 10-20 g:1L.
3. The preparation method according to claim 1, characterized in that: The preparation process of the nanofiber aqueous dispersion is as follows: adding nanofibers and a dispersing aid into water, dispersing them, and obtaining a uniform nanofiber aqueous dispersion.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the nanofibers to the dispersing aid is 1:(0.8-1.2).
5. The preparation method according to claim 1, characterized in that: The nanofiber has a morphology of at least one of a nanotube or a nanowire.
6. The preparation method according to claim 1, characterized in that: The aspect ratio of the nanofiber is (10-5000):
1.
7. The preparation method according to claim 1, characterized in that: The porous sound-absorbing material is at least one of polymer foam, cellulose board material or inorganic porous material.
8. The preparation method according to claim 1, characterized in that: The freeze-drying temperature is -70 to -18°C.
9. A composite porous material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite porous material according to claim 9 in the preparation of sound absorbing products.